Giant Sellar/Supra Sellar Arachnoid Cyst with Visual Loss: 5 Years Follow-Up Post Cystocisternostomy - Roka, Yam B; Bhattarai, Narayani R (Nepal Journal of Neuroscience, 2017)
Sellar/suprasellar arachnoid cyst can present with headache, endocrine dysfunction, psychomotor abnormalities, chronic hydrocephalus, vertigo, optic nerve and visual deficits and asymptomatically. We report a case managed with cystocisternostomy and long term follow-up with good improvement of his visual function. Nepal Journal of Neuroscience, Volume 14, Number 1, 2017, Page: 23-24